The affordances theory in teaching and learning African first additional languages: A case for task-based language teaching. Issue 1 (2nd January 2020) - Minas, Edith Christina
Abstract: Multilingual language policies in South Africa aim to promote tolerance and understanding of sociocultural differences and equal access to power. The current common curriculum for learning of all additional languages in South African primary schools presents negative affordances for the acquisition of African languages as second languages. This article proposes that task-based language teaching presents a set of language affordances for young beginner learners that is most conducive for the learning of an additional language in primary schools. The affordances theory in second language learning provides a lens that allows a single-minded focus on relevant issues in a complex and dynamic context. It considers the learning needs and goals of young learners and their teachers, and identifies language affordances in the learning process. The important role of the teacher in matching language teaching activities to individual learner's needs is recognised and justified in the affordances theory. Task-based language teaching presents a principled and empirically supported instructional approach, allowing a flexible methodology for teachers to achieve learning outcomes in diverse contexts.